Quantum Tourism in Bali: Integrating Cultural Heritage with Advanced Technologies for a Transformative Travel Experience - Ni Made Eka Mahadewi; Ida Bagus Putu Puja; I Wayan Mertha; Vijay Singh Rathore; Norol Hamiza Zamzuri (Pusat Kajian Bali Universitas Udayana, 2025)
Quantum tourism is an emerging phenomenon that integrates traditional tourism experiences with advanced technological, cultural, and spiritual dimensions. This study aims to explore the application of quantum tourism in Bali, analyzing how cultural and spiritual elements, alongside emerging technologies, can be synergized to enhance the tourism experience. The research employs a mixed method approach, where qualitative approach using interviews, data from previous studies, and quantitative approach using surveys with key stakeholders in Bali’s tourism industry. Combination of survey modes used were directed to the available sample frame. The findings enhance the conceptual understanding of quantum tourism by highlighting the quantum technology and central role of Bali’s spiritual energy, taksu, in shaping tourist experiences. However, the study also reveals the underutilization of advanced technologies such as IoT and AI. Findings suggest that, in times of uncertainty, investing in quantum technologies and sustainable practices could bolster Bali’s hotel, travel and tourism industry, ensuring it remains competitive and culturally authentic.